Analysis of Topic Dynamics in Web Search - Horvitz, Eric; Dumais, Susan (Proceedings of WWW 2005, 2005)
We report on a study of topic dynamics for pages visited by a sample of people using MSN Search. We examine the predictive accuracies of probabilistic models of topic transitions for individuals and groups of users. We explore temporal dynamics by comparing the accuracy of the models for predicting topic transitions at increasingly distant times in the future. Finally, we discuss directions for applying models of search topic dynamics.